Ethylene is a positive regulator of root hair development in Arabidopsis thaliana. - Tanimoto, M; Roberts, K; Dolan, L (1995)
Evidence is provided that ethylene is a positive regulator of hair cell development in the root epidermis of Arabidopsis thaliana. Treatment of seedlings with increasing concentrations of the ethylene precursor, 1-aminocyclopropane-1-carboxylic acid (ACC) results in progressively more root hair cells developing in positions normally occupied by non-hair cells. Consistent with these findings are observations that treatments that block either ethylene synthesis or its perception reduce the number of root hairs. A model is proposed in which either ethylene or ACC is a signal involved in specifying the pattern of cell differentiation in the Arabidopsis root epidermis.